The Effect of Flash Sale and Discount Towards Impulsive Buying (Study on Shopee Users) - Rhani Nastiti (Faculty of Economics and Business, Jenderal Soedirman University, 2020)
The purpose of this study is to explain the effect of flash sale and discount towards impulsive buying on Shopee users. This study used path analysis to determine the description of the variables studied and their effects, either directly, indirectly, partially or simultaneously on endogenous variables. Based on the results of the study indicate that there is the partial effect of flash sale and discount towards impulsive buying. Based on the the results of the study also showed that there is a positive effect simultaneously of flash sale and price discount towards impulsive buying in amount of 0,513 or 51,3%. Then the rest has amount of 0,487 so that the effect of variables not used in this variable has amount of 48,7% such as for example service quality, marketing costs, personal selling, and others.